Pollination Guilds of Aroids in Mulu National Park - Chai, Shong Kian (Universiti Malaysia Sarawak (UNIMAS), 2020)
The aroid flora of Borneo is one of the richest on the planet, comprising at least 800 species with many highly localized endemics. Not surprisingly, most of our knowledge of these taxa is limited to naming taxonomic novelties but beyond this, our knowledge on the pollination biology of Bornean aroids remains poor. Previous pollination research on aroid taxa on Borneo, revealed two pollination guilds: Diptera (Drosophilidae) and Coleoptera (Chrysomelidae, Hydrophilidae, and Staphylinidae) which are by far the major pollinating groups. This study was conducted at Gunung Mulu National Park, an area which hold one of the richest aroid diversity on Borneo, and aimed to determine pollinators of 21 selected aroids belonging to Tribe Aglaonemateae, Anadendrieae, Colocasieae, Homalomeneae, Monstereae, Potheae, Schismatoglottideae, and Thomsonieae. Extensive field observations on floral biology including stages of floral development, floral traits and rewards, identification of insect pollinators, and their behaviour(s) were carried out. The total anthetic time of most unisexually flowered taxa (Alocasia, Aglaonema, Homalomena, and Schismatoglottideae) lasted for two days, except Amorphophallus which ranged two to five days. In bisexually flowered taxa, Scindapsus completed anthesis in two days but anthesis lasted four days in Anadendrum and longer in Lasia and Pothos, which ranged 7-18 days. All investigated aroid taxa emitted floral odour during pistillate anthesis with several taxa (Anadendrum, Bucephalandra, Homalomena, Pothos, and Schismatoglottis pellucida) extended odour production until the end of anthesis. Some taxa (Amorphophallus and Pothos) do not restrict access to the pistillate flowers during pistillate anthesis. Diptera flies are the most possible pollinators for Alocasia, Aglaonema, Homalomena, Pothos, Schismatoglottideae and Scindapsus; Coleoptera beetles are the pollinators for Amorphophallus, Anadendrum, Homalomena, Lasia, and Schismatoglottis; Thysanoptera (thrips) are the pollinators of Anadendrum; Hemiptera are pollinators of Lasia and Pothos; Hymenoptera are pollinators of Alocasia sarawakensis and Amorphophallus hewittii. Floral rewards for pollinators included stigmatic secretion, floral tissues, and provision of mating sites.